The Glaciozyma Antarctica Genome Reveals An Array Of Systems That Provide Sustained Responses Towards Temperature Variations In A Persistently Cold Habitat - Mohd Firdaus-Raih; Noor Haza Fazlin Hashim; Izwan Bharudin; Mohd Faizal Abu Bakar; Kie Kyon Huang; Halimah Alias; Bernard K. B. Lee; Mohd Noor Mat Isa; Shuhaila Mat-Sharani; Suhaila Sulaiman; Lih Jinq Tay; Radziah Zolkefli; et al. (Public Library of Science (PLOS), 2024)
Extremely low temperatures present various challenges to life that include ice formation and effects on metabolic capacity. Psyhcrophilic microorganisms typically have an array of mechanisms to enable survival in cold temperatures. In this study, we sequenced and analysed the genome of a psychrophilic yeast isolated in the Antarctic region, Glaciozyma antarctica. The genome annotation identified 7857 protein coding sequences. From the genome sequence analysis we were able to identify genes that encoded for proteins known to be associated with cold survival, in addition to annotating genes that are unique to G. antarctica. For genes that are known to be involved in cold adaptation such as anti-freeze proteins (AFPs), our gene expression analysis revealed that they were differentially transcribed over time and in response to different temperatures. This indicated the presence of an array of adaptation systems that can respond to a changing but persistent cold environment. We were also able to validate the activity of all the AFPs annotated where the recombinant AFPs demonstrated anti-freeze capacity. This work is an important foundation for further collective exploration into psychrophilic microbiology where among other potential, the genes unique to this species may represent a pool of novel mechanisms for cold survival.